War and peace in outer space law, policy, and ethics - Hersch, Matthew H.; Steer, Cassandra (The Oxford series in ethics, national security, and the rule of law, 2021)
Historically, strategic restraint was the dominant approach among nations active in outer space, all of whom understood that continued access to and use of space required holding back on threats or activities which might jeopardize the status quo of peace in space. However, recently there has been a discernible shift in international rhetoric towards a more offensive approach to defense in space. The U.S. move towards establishing a "Space Force" has been echoed by similar announcements in France and Japan. India launched an anti-satellite weapon test and announced proudly that it thereby joined the elite group of China, Russia and the U.S., who have all demonstrated this capability in the past. And as technologies in space advance, along with our terrestrial dependence on space-based systems for our peaceful civilian lives and for support of terrestrial warfare, the political stability of this vulnerable environment comes under threat. These factors, combined with a lack of transparency about actual capabilities and intentions on the part of all major players in space, creates a cyclical escalation which has led some commentators to describe this as a return to a Cold War-type arms race, and to the foreseeability of a space-based conflict. Due to many unique characteristics of the space domain, an armed conflict in space would be catastrophic for all players, including neutral States, commercial actors, and international civil society. Due to the specificity of the space domain, specialized expertise must be provided to decision-makers, and interdisciplinary opinions must be sought from a multitude of stakeholders. To that end, this volume provides a wide spectrum of perspectives from experts who have engaged together at a conference hosted by the Center for Ethics in the Rule of Law to discuss these issues. Ethical, legal and policy solutions are offered here by those with experience in the space sector, including academia, legal practitioners, military lawyers and operators, diplomats and policy advisors"--